Incentivizing composting and tracking co2 emission reductions - building a mobile habit tracker using low-code - strategic recommendations for mudatuga - Reszel, Florian (2023)
Household composting represents a sustainable solution to deal with the negative externalities connected to food waste such as CO₂ emission and pollution. However, only a small number of households in Portugal have integrated home composting into their daily habits. On that basis, this report documents the conceptualization and implementation of Compostuga, a mobile habit tracker developed in collaboration with the impact start-up Mudatuga using low code technology. Compostuga incentivizes households to the continuous practice of composting through gamification and tracking of CO₂ emission reductions. Therefore, Compustuga will help to mitigate climate change by fostering low-carbon behavior among households. The thesis elaborates on the conceptualization of features regarding input and impact tracking and distinguishes how gamification contribute to the desirability of Compostuga. The thesis is finally concluded by making strategic recommendations about further development possibilities of Compostuga and Mudatuga as a company.